Efeito de técnicas da terapia manual sobre a modulação autonômica cardiovascular e o fluxo sanguíneo cerebral comparado a método placebo em saudáveis - Santana, Mylena Maria Salgueiro (2022)
Among physiotherapeutic modalities, it has been proposed that some techniques of manual therapy may influence Autonomic Nervous System (ANS). For that, there is an anatomical justification, where stimulation of spinal or paravertebral structures may lead to influence reflex responses of ANS, which in turn may alter visceral function. Such intervention methods are poorly understood as to their form of application, evaluation method, physiological justification, and there is no consensus about results found. Therefore, the main objective of this work is to determine whether the effects of the chosen manual therapy techniques, applied to healthy subjects, influence autonomic modulation and / or cerebral blood flow. To this end, the present project has already been approved by the Human Research Ethics Committee (CAAE: 47522315.2.0000.5546). Subjects between 18 and 30 years old, of both sexes, were recruited randomly into 4 groups: Intervention Group 1 (atlanto-occipital joint decompression technique) Intervention Group 2 (fourth ventricle decompression technique); Intervention Group 3 (stretch-relax technique of the suboccipital muscles) and Group 4 (placebo). All subjects went through an adaptation phase, during 10 minutes, in the supine position. After that, they received the techniques or the placebo for 05 minutes, and the data were collected again for another 10 minutes. During the entire collection, the subjects were attached to the Finapres device, where heart rate and blood pressure are recorded beat by beat. Before and after the application of the techniques, in the 10 minutes before and after the intervention, the individuals were also evaluated using transcranial Doppler, which measures the speed of cerebral blood flow, analyzing the middle cerebral artery. It was observed that, regarding the SNA variables analyzed in the frequency domain, there was no statistically significant difference in any of the groups analyzed. Regarding the speed of cerebral blood flow, there was a statistically significant difference for the stretching groups to contract relax and decompression of the atlanto-occipital joint, with an increase in speed in Group 3 and a decrease in Group 4. Apparently, the techniques applied in this study, did not interfere with cardiac autonomic modulation; the cerebral blood flow, on the other hand, obtained changes in its speed in two techniques, those that, in fact, alter and sustain the change in the positioning of vertebral structures that can cause stenosis or release of the region. Thus, it is believed that manual therapy techniques do not have systemic autonomic effects, but small local changes in terms of blood flow.